Roots - Alex Haley (USA Dell Publishing Co, 1977)
Drawing on the oral traditions handed down in his family for generations, the author traces his origins back to the seventeen-year-old Kunta Kinte, who was abducted from his home in Gambia and transported as a slave to colonial America. In this account Haley provides an imaginative rendering of the lives of seven generations of black men and women.
"A condensed version of a portion of this work first appeared in Reader's digest."
Keywords: Literature (3GdCOHs; General